Waterlogging response in BH_22 population of Urochloa humidicola - Barbosa, Norma; Garzon, Maria Jose (2025)
Among different forages, there have been some commercial grasses well characterized in tolerating the conditions of waterlogging soils, for example, Urochloa humidicola. This species has shown the maintenance of growth rate, leaf elongation, net photosynthesis, and leaf chlorophyll content (Dias-Filho & Carvalho, 2000). Despite this, variations in morphological traits, forage production and waterlogging tolerance level have been found among U. humidicola accessions. Therefore, knowing its performance during esters conditions of waterlogging is important (Cardoso et al., 2013). Based on this among the 80 genotypes, there exist plant genotypes with varying levels of resistance to waterlogging conditions, with some genotypes demonstrating significantly higher resistance based on their productivity metrics. The objective is to identify plant genotypes with the greatest resistance to waterlogging stress based on their productivity, and to evaluate the correlation between productivity and other variables.